A new species, Bulbophyllum mamillatum and a new national record, B. retusum (Orchidaceae) in the flora of Vietnam - Van Tu Nguyen (Taiwania, 2022)
Bulbophyllum mamillatum Vuong, Aver., V.S.Dang is described as a new species for science and B. retusum H. Jiang, D.P. Ye & J.D. Ya is reported as a new national record for the orchid flora of Vietnam. Both species belong to Bulbophyllum sect. Brachyantha Rchb.f. and were discovered in northern Vietnam. Description of new the species is presented. Data on habitat, phenology, distribution, conservation status, and taxonomic notes for both species are provided.